Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Pegawai pada Kantor Inspektorat Kabupaten Sikka - Yohana Ivonista; Antonius Phillipus Kurniawan; Imelda Virgula Wisang (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The background of this research is the employee performance of the Inspectorate Office in Sikka Regency has not been maximized. This research aimed to (1) determine the decription of work performance, work load, and work stress at the Inspectorate Office In sikka Regency and (2) analyze the influence of workload and work stress on the employee performace of the Inspectorate Office in Sikkaregercy both partially and simultaneously. The population in this research were employess of the Inpectorate Office in Sikka Regency totaling 43 people . This research was carried out by continuing to census or saturated sampling because the population was limited. Data were coocted though questionnaires and analyzed thoghdescriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done though the F and t-tests. The result of descriptive analysis indicatend that the employe performance, workload,and work stress variables were categorized as good. The statistical results of the F-test showed that together ( simultaneously ) all independemt variables consisting of workload variable (X1) and work stress variable ( X2) had a significant influence on employee performance.The statistical result of the t-test showed that individually (partially ) the workload variable ( X1) had a significant influence on the employe performance variable and then partially the work stress variable had a significant influence on the employee performance variable at the Inspectorate Office in Sikka Regency . The results of the determination analysis showed that the two independent variables in this research were able to explain the variation in the variation in the ups and downs of employee performance of 28.2%.